The Influence of Ewom on Mindful Consumption Behavior Mediated by Attitude, Religiosity, and Mindfulness - Bunga Agustina Perdani; Rini Kuswati; Moechammad Nasir (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this study is to analyze the influence of Ewom on mindful consumption behavior mediated by Attitude, Religiosity, and Mindfulness. This research employs an explanatory quantitative approach. The population in this study consists of consumers who actively use digital media to search for information about products and receive information from electronic word of mouth (eWOM), particularly those with experience purchasing thrift products. The data in this study are primary. The sampling technique employed in this study is a non-probability sampling approach based on purposive sampling. Data analysis techniques utilize PLS-SEM Software, specifically SMARTPLS. PLS-SEM analysis consists of two parts: the outer model and the inner model. The outer model analysis includes validity testing, reliability testing, and multicollinearity testing. The inner model analysis includes model Goodness testing and hypothesis testing. The results of this study indicate that EWOM has a positive and significant influence on Mindful Consumption Behavior. EWOM has a positive and considerable impact on Attitude. EWOM has a positive and significant effect on Religiosity. EWOM has a positive and substantial influence on Mindfulness. Attitude has no considerable effect on Mindful Consumption Behavior. Religiosity has a positive and significant impact on Mindful Consumption Behavior. Mindfulness has a positive and significant effect on Mindful Consumption Behavior. Attitude does not mediate the relationship between EWOM and Mindful Consumption Behavior. Religiosity mediates the impact of EWOM on Mindful Consumption Behavior. Mindfulness mediates the relationship between EWOM and Mindful Consumption Behavior.